Practices of Future Foresight in Management of Non-Communicable Diseases -An Early Attempt towards Focusing on ‘Foresight Economy’ Labs. - Buheji, Mohamed (Advances in Social Sciences Research Journal, 2018)
Future foresight have been more linked with technological changes and innovative disruptions than socio-economic challenges. With the development of foresight, science efforts should be directed towards tackling humanity chronic problems than just focusing most of the efforts on future technological developments and advancements only. Focusing the foresight analysis on the increase of Non-Communicable Diseases (NCD’s) doesn’t only help us to tackle current and future health community issues, but in fact direct the focus of the efforts on mitigating the progressive development of future socio-economic and quality of life challenges. The world need more work in utilising strategic foresight in dealing with Socio-Economic challenges. The holistic approach of SF studies targeted to overcome the usual challenges that face the future socio-economic change where NCD’s are expected to become more of epidemic problem in many countries and specially in the Arab and Asian emerging economy countries. The future carries a catastrophic result where 90% of the population in a country like Bahrain might be at risk of NCD during their life in the next 50 years, unless radical lifestyle changes are done. Utilising a technique called ‘foresight economy’ lab (FEL) the problem statement is shifted from solutions of increasing the NCD’s clinics in Community Health Centre (CHC’s) to more challenging the CHC’s staff towards better explore early NCD’s risks, i.e. focusing in increasing their capacity through collaboration of all the community services. This paper concludes with what FEL’s bring in as opportunities that would help in drastically reducing the percentage of population at NCD’s risk, from having 90% to 50% at risk in 20 years from now and with minimal resources.